Patient satisfaction with treatment outcomes after surgery and/or radiotherapy for spinal metastases. Issue 23 (6th September 2019) - Versteeg, Anne L.; Sahgal, Arjun; Kawahara, Norio; Rhines, Laurence D.; Sciubba, Daniel M.; Weber, Michael H.; Lazary, Áron; Fehlings, Michael G.; Schuster, James M.; Clarke, Michelle J.; Arnold, Paul M.; Boriani, Stefano; et al.
Abstract : Background: Patient satisfaction is infrequently investigated despite its importance in assessing efficacy and patient comprehension. The purpose of this study was to investigate patient satisfaction with treatment outcomes after surgery and/or radiotherapy for spinal metastases and to evaluate how health‐related quality of life (HRQOL) is related to patient satisfaction. Methods: Patients with spinal metastases treated with surgery and/or radiotherapy were enrolled in a prospective, international, observational study. Demographic, histologic, treatment, and HRQOL data were collected. HRQOL was evaluated with the Numeric Rating Scale pain score, the 3‐level version of the EuroQol 5‐Dimension (EQ‐5D‐3L) instrument, and the Spine Oncology Study Group Outcomes Questionnaire (SOSGOQ2.0). Patient satisfaction was derived from the SOSGOQ2.0 at 6, 12, and 26 weeks after treatment. Patients were classified as satisfied, neutral, or dissatisfied. Results: Twelve weeks after treatment, 183 of the surgically treated patients (84%) were satisfied, and only 11 (5%) were dissatisfied; in contrast, 101 of the patients treated with radiotherapy alone (77%) were satisfied, and only 7 (5%) were dissatisfied. Significant improvements in pain, physical function, mental health, social function, leg function, and EQ‐5D were associated with satisfaction after surgery. Satisfaction after radiotherapy was associated with significant improvements in pain, mental health, and overall SOSGOQ2.0 scores. Dissatisfaction after treatment was associated with lower baseline values for leg strength and lower social functioning scores for surgically treated patients and with lower social functioning scores and being single for patients treated with radiotherapy. Conclusions: High levels of satisfaction with treatment outcomes are observed after surgery and/or radiotherapy for spinal metastases. Posttreatment satisfaction is associated with significant improvements in pain and different dimensions of HRQOL. Abstract : High levels of satisfaction with treatment outcomes are observed after surgery and/or radiotherapy for spinal metastases. Posttreatment satisfaction is associated with significant improvements in pain and different dimensions of health‐related quality of life.